Understanding the sugar beet holobiont for sustainable agriculture - Wolfgang, Adrian; Temme, Nora; Tilcher, Ralf; Berg, Gabriele (Frontiers in Microbiology, 2023)
The importance of crop-associated microbiomes for the health and field performance of plants has been demonstrated in the last decades. Sugar beet is the most important source of sucrose in temperate climates, and - as a root crop - yield heavily depends on genetics as well as on the soil and rhizosphere microbiomes. Bacteria, fungi, and archaea are found in all organs and life stages of the plant, and research on sugar beet microbiomes contributed to our understanding of the plant microbiome in general, especially of microbiome-based control strategies against phytopathogens. Attempts to make sugar beet cultivation more sustainable are increasing, raising the interest in biocontrol of plant pathogens and pests, biofertilization and –stimulation as well as microbiome-assisted breeding. This review first summarizes already achieved results on sugar beet-associated microbiomes and their unique traits, correlating to their physical, chemical, and biological peculiarities. Temporal and spatial microbiome dynamics during sugar beet ontogenesis are discussed, emphasizing the rhizosphere formation and highlighting knowledge gaps. Secondly, potential or already tested biocontrol agents and application strategies are discussed, providing an overview of how microbiome-based sugar beet farming could be performed in the future. Thus, this review is intended as a reference and baseline for further sugar beet-microbiome research, aiming to promote investigations in rhizosphere modulation-based biocontrol options.